Investigating ward nurses’ perceptions of hospital pharmacy service quality: The case of a South African Private Hospital Group (Al-Sihah : The Public Health Science Journal, 2025)
In recent years, organisations have increasingly focused their attention on internal service quality, which has a significant effect on customer satisfaction, which in turn impacts the performance of the organisation and ultimately profitability. However, there is limited research locally and/or internationally that has investigated the internal service quality provided to nursing staff by the hospital’s pharmacy. This study investigated ward nurses’ perceptions of service quality provided by the hospital pharmacy of a hospital group in South Africa. The quantitative survey drew on the work of Hollis, who identified eleven dimensions of internal service quality in a health context. Data was collected via a questionnaire comprising 47 question items, on a 5-point Likert scale, distributed to over 700 registered ward nurses to seven acute hospitals in the province of KwaZulu-Natal in South Africa. Factor analysis identified six latent factors that influenced the ward nurses’ perception of the hospital pharmacy’s service quality. The factors identified (with Cronbach Alpha values provided) were courtesy (0.937), caring (0.936), reliability (0.930), equity (0.867), competence (0.866), and communication (0.771). The findings suggest that a more compact version of the dimensions of Hollis seems relevant in the private hospital setting, with the principles of Ubuntu contributing to better service quality. The findings of this study could help improve the current level of the internal service quality that hospital pharmacies provide to ward staff by focusing on the dimensions identified and drawing on Ubuntu principles. It can also provide management with focus areas for improving internal service quality.